TRILHOS MATEMÁTICOS COMO CONTEXTO PARA O ENSINO E A APRENDIZAGEM DE GEOMETRIA ESPACIAL COM ESTUDANTES DO TERCEIRO ANO DO ENSINO MÉDIO - Gehrke, Tatiéle Tamara (2017)
The purpose of this dissertation is to answer the following problem: How the proposition and resolution of problems created from the observations collected through the realization of a Mathematical Trail in the environment in which the students live can contribute to the teaching and learning of geometric solids with students of the third year of High School? The objective is to investigate if the proposition and resolution of problems created from the observations collected through the accomplishment of a Mathematical Rail in the environment in which the students live contributes to the teaching and learning of the geometric solids with students of the third year of High School. The subjects that participated in the research were students of the 3rd year of the High School of the State School of Secondary Education Presidente Afonso Pena, in the city of Paraíso do Sul / RS. The research was qualitative, based on the ideas of Van Hiele on the development of geometric thinking and Problem Solving. The instruments used involved a diagnostic test, the accomplishment of the Mathematical Trail, the didactic sequence elaborated by the students based on the data collected on the trail and the didactic sequence elaborated by the teacher-researcher, besides a class diary in which the events occurred in Classroom and the documents produced in the productions and resolutions of the problems. The activities developed in the didactic sequences were planned taking into account the levels of Van Hiele, in order to assist in the development of geometric reasoning. After the activities developed and the results analyzed, it was found that the students felt involved with the proposed activities, especially in relation to the Mathematical Trail, from which they could observe and create problems according to their observations in a familiar environment. In addition, it can be concluded that the Problem Solving methodology was valid because it enabled the students to carry out a collective and collaborative work, in addition to favoring the construction of knowledge in a participatory manner.